Upaya Meningkatkan Hasil Belajar Peserta Didik Melalui Model Pembelajaran Conceptual Attainment Pada Pembelajaran Sosiologi Di Kelas XI IPS SMAN 13 Padang - Khairida Syafriza; Junaidi Junaidi (Universitas Negeri Padang, 2022)
This research is motivated by the low learning outcomes of students in class XI IPS 3 at SMAN 13 Padang compared to other class XI IPS, even though all class XI IPS at SMAN 13 Padang are taught by the same educator. The purpose of this study was to improve student learning outcomes by applying the Conceptual Attainment learning model to Sociology learning in class XI IPS 3 SMAN 13 Padang. The research method used is a quantitative approach. The type of research used is Classroom Action Research (CAR) and uses the Conceptual Attainment learning model. This study uses the Kemmis and Taggart research design model which is carried out in several cycles, each cycle consists of 4 stages namely, Planning, Action, Observation, Reflection and this research consists of 2 cycles, each cycle consists of two meetings. Data collection techniques in this study using Observation, Interview, Documentation, and Tests. The data analyzed used in this research are qualitative analyzed and quantitative analyzed. Qualitative data were obtained from observations, interviews, and documentation during the research activities. Quantitative data obtained from student learning outcomes and this study used construktivist learning theory. The application of the Conceptual Attainment learning model can improve the learning outcomes of students in class XI IPS 3 at SMAN 13 Padang in the 2021/2022 school year. overall student learning outcomes increased from the pre-action stage, cycle 1 and cycle 2. Where in the pre-action stage the average student learning outcomes were 71.28, in cycle 1 the average student learning outcome was 74.35 and in cycle 2 the average learning outcomes of students are 80. Based on the results of research that researchers did while at SMAN 13 Padang, it can be concluded that using the Conceptual Attainment learning model can improve student learning outcomes in class XI IPS 3 SMAN 13 Padang .